Histomorphology of the lower respiratory tract in the Indian crested porcupine (Hystrix indica) - Marzban Abbasabadi, Behrokh; Moradi, Hamid Reza; Arefi, Shirin; Kyllar, Michal (Anatomia, histologia, embryologia, 2021)
The Indian crested porcupine (Hystrix indica) (ICP) is widely distributed in Asia; however, compared with other rodents, little is known about the structures of its respiratory system. The aim of this study was to evaluate the histomorphology of the lower respiratory portion of the ICP to provide a basis for the identification of the normal structure of this organ. The larynx, trachea and lungs of four carcasses of adult Indian crested porcupines (two males and two females) were dissected and fixed in 10% neutral-buffered formalin. The gross anatomy and histology of all specimens were evaluated. A macroscopic evaluation showed unique structures in the ICP respiratory system, including the presence of a chamber-like structure at the origin of the bronchi and a difference in epiglottis shape between males and females. Histologically, the stratified squamous epithelium covered the epiglottis and arytenoid cartilage, and the pseudostratified ciliated columnar epithelium covered the internal part of the thyroid and cricoid cartilages. Histomorphological studies showed a few goblet cells in the tracheal epithelium. In the bronchi and larger bronchioles, pseudostratified ciliated columnar epithelia were observed. Bronchi were surrounded by segments of cartilage. Distal bronchioles had a simple cuboidal/columnar epithelium with club (Clara) cells, lacked cartilaginous tissue in their walls and had a complete smooth muscle layer. These results revealed histomorphological differences between the ICP and other rodents.
Keywords: dikobrazovití a urzonovití; lung; epitel; Trachea; bronchy; Bronchi; Female; Indian crested porcupine; Lung; larynx; zvířata; respiratory system; plíce; ženské pohlaví; trachea; Male; Epithelium; porcupine; Animals; mužské pohlaví; Porcupines